Implications of floristic patterns, and changes in stand structure following a large-scale, intense fire across forested ecosystems in south-Western Australia's high-rainfall zone - Wardell-Johnson, Grant; Luxton, S.; Craig, K.; Brown, V.; Evans, N.; Kennedy, S. (Surrey Beatty and Sons, 2017)
The isolated forested ecosystems of south-Western Australia are experiencing warming, drying, and increasing wildfires. How are these changes impacting on biodiversity in the region? A wildfire burnt over 98000ha in the high-rainfall ( > 1100mm) zone between Northcliffe and Walpole in January-February 2015. A lack of permanent plots limited assessment of impact. However, plot establishment in September 2016 enabled benchmarking of local biodiversity responses in areas burnt at high intensity 18 months previously. We assessed floristic composition, fire response traits and vegetation structure in 48 plots (each 78.5m2) replicated equal ly across four neighbouring vegetation types (tall open-forest, open-forest, low open-forest and shrubland). We recorded 165 vascular plant species across these four environments, which differed in environmental profiles, species density, fire trait syndromes and fire-determined structural responses. Shrubland (77 species) was most dominated by geophytes and rhizomatous taxa; and open-forest (82 species) and tall open-forest (41 species) by soil-stored seeders. Epicormic resprouters were dominant in all three forest types. Considerable impact was observed in tree structure, suggesting that recovery in height and biomass in forested vegetation will take longer than fire-return times under trends of increasing frequency and intensity of wildfire in the region. In light of these findings we advocate fire management regimes that reduce the impact of on-going climate trends. These are mosaics that take advantage of moisture differentials, sharp ecotones and different suites of fire response syndromes, and target high-value assets for protection.